2022
DOI: 10.1186/s40779-022-00378-z
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine modification of CENPK mRNA by ZC3H13 promotes cervical cancer stemness and chemoresistance

Abstract: Background Stemness and chemoresistance contribute to cervical cancer recurrence and metastasis. In the current study, we determined the relevant players and role of N6-methyladenine (m6A) RNA methylation in cervical cancer progression. Methods The roles of m6A RNA methylation and centromere protein K (CENPK) in cervical cancer were analyzed using bioinformatics analysis. Methylated RNA immunoprecipitation was adopted to detect m6A modification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…ZC3H13 expression was shown to be drastically reduced in endometrial carcinoma tissues in a prior study, and it was found to inhibit endometrial carcinoma cell lines from increasing proliferation and invasion (34). ZC3H13 enhanced stemness and chemoresistance via modulation of CENPK mRNA in cervical cancer cells (35). However, the relevance of METTL16 and ZC3H13 in cervical cancer is still not fully known.…”
Section: Discussionmentioning
confidence: 98%
“…ZC3H13 expression was shown to be drastically reduced in endometrial carcinoma tissues in a prior study, and it was found to inhibit endometrial carcinoma cell lines from increasing proliferation and invasion (34). ZC3H13 enhanced stemness and chemoresistance via modulation of CENPK mRNA in cervical cancer cells (35). However, the relevance of METTL16 and ZC3H13 in cervical cancer is still not fully known.…”
Section: Discussionmentioning
confidence: 98%
“…Lin et al. [ 231 ] found that ZC3H13‐mediated m 6 A modification of CENPK mRNA promoted cervical cancer stemness and chemoresistance (Fig. 6B ).…”
Section: The M 6 a Modification In Chemoresistancementioning
confidence: 94%
“…6A). Lin et al [231] found that ZC3H13-mediated m 6 A modification of CENPK mRNA promoted cervical cancer [204]. (B) METTL14-mediated m 6 A modification on THBS1 mRNA promotes YTHDF2-mediated THBS1 decay in PRAD cells [205].…”
Section: Regulation Via M 6 a On Mrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional bulk genomic and transcriptomic analyses average signals from a group of different cells, which obscures the identification of specific cell types and states. In situ hybridization and immunohistochemistry have been used to explore the genomic, transcriptomic, and proteomic characteristics of individual cells, but their outputs are relatively low [ 15 , 16 ]. Flow cytometry and cytometry by time-of-flight (CyTOF) are capable of analysing thousands or millions of single-cell proteomic profiles [ 17 ]; however, these methods require prior selection of antibodies of interest.…”
Section: Introductionmentioning
confidence: 99%